(untitled) (Research, Society and Development, 2023)
The ketogenic diet (KD) consists of a nutritional regimen rich in lipids, moderate in proteins and low in carbohydrates, which has been shown to be important compared to conventional cancer treatments due to its role in the metabolic reprogramming of tumor cells. The objective of this research is to carry out a narrative review on the impact of using CD as a complementary strategy in cancer treatment. The methodology used was a narrative and qualitative review on the subject in question. 10 articles were selected for analysis, chosen from among 19 articles resulting from the database search. Among the studies evaluated, a higher incidence of studies was observed in the United States with 5 articles, then Iran with 2 articles and finally Germany, Canada and the United Kingdom with 1 study each. Regarding the types of CA, there was wide diversity involved in the studies. Ovarian and endometrial CA with 3 articles, Glioblastoma with 2, Prostate CA with 1 and breast CA, the latter being the most common, with 4 articles published. The year in which there were the highest number of studies on the subject was in 2020, with 4 articles published. After 2018 and 2019 with 2 articles. And finally 2021 and 2022 with only 1 article published on the topic in our chosen database. It was possible to conclude that the observed impact of CD on cancer patients is beneficial and promising as a complementary treatment. Its effectiveness in reducing tumors, regulating body weight, preventing loss of muscle mass, preventing cachexia and regulating blood glucose is evidente.